Aerogel-based renders with lightweight aggregates: Correlation between molecular/pore structure and performance. (15th October 2016) - de Fátima Júlio, Maria; Soares, António; Ilharco, Laura M.; Flores-Colen, Inês; de Brito, Jorge
Graphical abstract: Highlights: A thermal render with cement-fly ash, subcritical hybrid aerogel and co-aggregates. T1 thermal render with suitable compressive strength and good deformation capacity. The lightweight aggregates mixture enhances hygrothermal and mechanical performance. Correlation between molecular and pore structure and performance. Abstract: The role of lightweight aggregates on the hygrothermal and mechanical performance of cementitious aerogel-based renders was understood. The lightweight aggregates totally replaced silica sand, with a binder:aggregate volume ratio of 1:4. A cement-fly ash (50 wt%) binder, with 60 vol% subcritical silica-based aerogel, 20 vol% granular expanded cork, 15 vol% expanded clay and 5 vol% perlite, produces a lightweight (652 kg.m −3 ), thermal render (thermal conductivity of 0.084 W.m −1 .K −1 ), with acceptable mechanical strength and good deformation capacity. The correlation of these renders' properties with the molecular and pore structure of the aggregates proved to be extremely useful to improve their overall performance.